3D micromechanical modelling of unidirectional carbon fibre reinforced composites - Tiong, Matthew Kwong Hoong. (2012)
This project aims to create a computational model to simulate the tensile behaviour of a unidirectional carbon fibre reinforced composite with a porous matrix. The focus of the project was to analyse the effects of porosity on the properties of the composite. The finite element software used in this project was ABAQUS FEA.